Emery-Dreifuss muscular dystrophy: localisation to Xq27.3----qter confirmed by linkage to the factor VIII gene. Issue 6 (December 1986) - Yates, J R; Affara, N A; Jamieson, D M; Ferguson-Smith, M A; Hausmanowa-Petrusewicz, I; Zaremba, J; Borkowska, J; Johnston, A W; Kelly, K
Abstract : Two families with Emery-Dreifuss muscular dystrophy (EMD) have been studied with DNA markers mapping to Xq27.3----qter. No recombination was observed in 11 phase known meioses informative for the factor VIII gene (F8C) and eight phase known meioses informative for DXS15 (DX13), giving maximum lod scores of 3.50 and 2.50 respectively at a recombination fraction of zero. DXS52 (St14) showed one recombinant in 12 phase known meioses giving a maximum lod score of 2.62 at a recombination fraction of 0.07. These results map EMD to the distal end of the long arm of the X chromosome and are an important step in the development of tests for carrier detection and prenatal diagnosis.